A study of production outsourcing strategies of dual oligopoly manufacturers based on quality investments - Wang, Yang; Deng, Tongbo; Cheng, Huibing (Frontiers in Physics, 2024)
Improving product quality is an important driver for production outsourcing. This paper constructs production outsourcing game models for duopoly manufacturers, examines the trade-offs between self-production and outsourcing when suppliers have the ability to invest in quality, explores the requirements and implications of outsourcing and compares the differences between "one-to-one" and "one-to-many" outsourcing structures. The results show that, first, outsourcing can reduce the level of product quality and that a necessary condition for manufacturers' outsourcing is a strong advantage in the supplier's production costs. Second, duopoly manufacturers may face a prisoner's dilemma as a result of outsourcing. Finally, compared to two independent suppliers, outsourcing to a common supplier can increase the level of product quality by exploiting the centralization effect and increase the firm's profits when the market's competition intensity is low. The results can help foundry suppliers and manufacturers make production decisions.